(untitled) (Research, Society and Development, 2019)
The present work reports a proposal for the restructuring of the discipline of Control Systems I for undergraduate students of Control and automation engineering of UFMT. The discipline followed the traditional learning model and the new proposal contemplates the project based learning (PjBL). The objective of this experiment is to motivate students to become more central to the solution of real engineering problems, developing functional prototypes throughout the course. It is concluded that the applied proposal has great potential as a learning method and can also be applied in other engineering disciplines that involve theory and practice, since it increases the students’ involvement with the project since their beginning. The idea was highly accepted by the students and the authors suggest questionnaires that evaluate students’ learning to reduce traditional classes where the teacher was the sole source of knowledge and increase the students’ active behavior.